2017
DOI: 10.1007/s10734-017-0126-0
|View full text |Cite
|
Sign up to set email alerts
|

Leadership for team learning: the case of university teacher teams

Abstract: Teacher team involvement is considered a key factor in achieving sustainable innovation in higher education. This requires engaging in team learning behaviors that should result in new knowledge and solutions. However, university teachers are not used to discussing their work practices with one another and tend to neglect any innovation in their tasks. Team leadership behavior is often considered essential for stimulating team learning behavior, but it is unclear how this transpires. Therefore, the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 56 publications
(126 reference statements)
5
34
0
5
Order By: Relevance
“…These findings that point towards the need for an ambidextrous team leader confirm the studies of Bucic et al (2010) and Koeslag-Kreunen et al (2017), who found that characteristics of both a transformational and transactional leadership style can contribute to team learning. The findings are also aligned with the review study of Rosing et al (2011), who argued that leaders need to switch between 'opening leader behaviours' (similar to transformational leadership) and 'closing leader behaviours' (similar to transactional leadership) during innovation tasks, for example designing, redesigning and implementing CBE.…”
Section: Leadership Ambidexteritysupporting
confidence: 86%
See 3 more Smart Citations
“…These findings that point towards the need for an ambidextrous team leader confirm the studies of Bucic et al (2010) and Koeslag-Kreunen et al (2017), who found that characteristics of both a transformational and transactional leadership style can contribute to team learning. The findings are also aligned with the review study of Rosing et al (2011), who argued that leaders need to switch between 'opening leader behaviours' (similar to transformational leadership) and 'closing leader behaviours' (similar to transactional leadership) during innovation tasks, for example designing, redesigning and implementing CBE.…”
Section: Leadership Ambidexteritysupporting
confidence: 86%
“…Based on these findings, it is suggested that ambidextrous leadership is needed to stimulate teachers' team learning, which is confirmed by previous research (Bucic et al, 2010;Koeslag-Kreunen et al, 2017). This implies that during certain tasks and challenges teacher teams benefit from control and direction instead of autonomy, while during other tasks and challenges they benefit more from autonomy.…”
Section: Teachers' Perceptions and Team Learningsupporting
confidence: 76%
See 2 more Smart Citations
“…The impression that transformational leadership theory may be valuable in higher education institutions is supported by a meta-analytic review (Balwant 2016). Transformational leadership behaviors appear to upkeep team learning via stimulating spirit at work and team efficacy (Koeslag-Kreunen et al 2018). As the higher education institutions have become increasingly concerned with key performance indicator KPI -led planning and strategy, therefore it is imperative that the leaders of higher educational institutions walk the talk, share responsibility with formal and informal leaders from faculty and staff group and practice what they preach through transformational leadership behavior.…”
Section: Introductionmentioning
confidence: 99%